Pengaruh Metode Partisipatori terhadap Kemampuan Menulis Teks Deskripsi - Berbudi, Gina Julia; Anwar, Nanang Chaerul; Setiadi, David (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to examine the effect of participatory methods on the ability to write descriptive text for grade VII students of SMP Negeri 1 Sukabumi City in 2018/2019 Academic Year. The main subjects in this study were students of class VII G, amounting to 36 students. The purpose of this research is to know the ability to write description text before and after using participatory methods, and determine the effect of participatory methods on the ability to write descriptive text. The research method used in this study is a quantitative method using a one group pretest-posttest design research design. The results of the study were obtained when the pretest average value of students is 40 while the posttest average value of 65.41. This has increased after researchers used participatory methods. The results of the calculation of each test were carried out using the t-test and it was significant to pretest and posttest so that the results obtained were tcount (12.29)> ttable. These results indicate a difference that occurs between the pretest and posttest. It can be concluded that participatory learning methods affect the ability to write description texts for grade VII students of SMP Negeri 1 Sukabumi. Keywords: Writing, Description Text, Participatory